Determining the Prognostic Value of Coagulation Parameters and D-dimer Plasma Level in Admitted COVID-19 Patients - Maryam Ghasemi; Somayeh Sheidaei; Elahe Kavoosi; Mohammad khademloo; Parvaneh Afshar; Fatemeh Abedian (Research in Molecular Medicine)
Background: Severe acute respiratory syndrome coronavirus2 (SARS-CoV-2) has emerged as a global concern. Since its outbreak in December 2019, researchers and authorities have made numerous efforts to identify the disease’s prognostic markers. Changes in the values of coagulation tests are common in these patients. This study aimed to study any possible association between coagulation parameters in COVID-19 patients with prognostic indicators and the disease severity. Methods: This cross-sectional survey investigates the CBC, coagulation status, and plasma D-dimer level in confirmed cases of COVID-19 (RT-PCR and/or chest CT scan) admitted to Boo-Ali Sina and Imam Khomeini hospitals affiliated with Mazandaran University of Medical Sciences, in the north of Iran in the last three months of 2021. The tests were ordered at the beginning of hospitalization and discharge. The results included lung involvement percentage, intensive care unit (ICU) admission, and survival. Results: Of 140 COVID-19 patients (Mean±SD age: 55.73±16.821 years) evaluated in this study, 51.4% were male. Among comorbidities, diabetes and hypertension were the most common ones. The Mean±SD hospitalization length was 8.47±7.8 days. Also, 56(40.0%), 40(28.6%), and the rest of the patients showed <25%, 25%-50%, and >50% of lung involvement, respectively. In addition, the CURB-65 score for pneumonia severity was low, medium, and high risk for 84, 34, and 22 patients, respectively. The most frequent abnormality among the results was prothrombin time (PT) (17.9%), thrombocytopenia (25.7%), partial thromboplastin time (PTT) (32.9%), and elevated D-dimer level (62.9%). The results showed a significant relationship between abnormal D-dimer levels and poor outcomes, including higher CURB-65 score, higher lung involvement in CT scans, more ICU admissions, and even death. Meanwhile, PT, PTT, and platelet count on admission did not help predict the study population’s clinical course and general survival. Conclusion: Disturbance of coagulation parameters in COVID-19 patients with no significant history can serve as an available and reliable prognostic marker in the patients’ outcomes and clinical course.